Razvoj modela procesa in strukture krmilnega sistema delovne enote za indukcijsko kaljenje - Cajner, Franjo (Strojniški vestnik, 1999)
In order to achieve higher quality and a more flexible execution of the induction hardening process, a computer assisted program for undertaking and controlling of this process is needid. This paper proposes and drscribes a model for the induction hardening process, the application of which achieves a specified quality of the hardened layer, within all parameters of the process. All the influencing factors, which define and implement the control environment used in the application of the process within the flexible working cell, are systematically analyzed.
Keywords: kaljenje induktivno; modeliranje procesov; sistemi krmilni; celice fleksibilne; krmilni sistemi; toplotna obdelava; kaljenje; modeliranje; krmiljenje